Adaptive amplifier system for sensor network applications - Lovay, Mónica (2011)
This paper presents an adaptive amplifier that is part of a sensor node in a wireless sensor network. The system presents a target gain that has to be maintained despite the presence of faults while its bandwidth must be as large as possible, without direct human intervention. The system is composed by a software-based built-in self-test scheme implemented in the node that checks all the available gains in the amplifiers, a reconfigurable amplifier and by a genetic algorithm (GA) for reconfiguring the node resources that runs in a host computer. We adopt for the node implementation a PSoC device from Cypress. The performance evaluation of the scheme presented is made by adopting two different types of fault-models in the amplifier gains. The fault simulation results show that GA finds the target gain with low error, maintains the bandwidth above the minimum tolerable bandwidth and presents a run time lower than an exhaustive search method.